An Empirical Analysis of the Flotation Cost of Corporate Securities, 1971- 1972 - Johnson, Keith B.; Morton, T. Gregory; Findlay, M. Chapman (Journal of Finance, 1975)
Keith B. Johnson, T. Gregory Morton, M. Chapman Findlay, III, An Empirical Analysis of the Flotation Cost of Corporate Securities, 1971- 1972, The Journal of Finance, Vol. 30, No. 4 (Sep., 1975), pp. 1129-1133